Aplicación de técnicas de pentesting para determinar vulnerabilidades en la red lan de la Empresa CSEDNET de Santo Domingo - Vera Correa, Jairo Alexander (2021)
The objective of this research is to identify the vulnerabilities that the LAN network of the company CSEDnet from Santo Domingo has through the application of the pentesting tests: sniffing and parameter tampering, so that, based on the problems found, to be able to generate policies security and apply them in the infrastructure and the main active equipment of the LAN network. To this end, the research question is the following: How will the implementation of an information and network assurance plan mitigate unwanted infiltrations in the CSEDnet company? In this context, computer security is a very important aspect to take into account for companies that, at a minimum, use and have LAN networks to develop their work activities, since the information that is transmitted through this network is of vital importance for those who form part of the institution and its clients. The phases of the CEH (Certified Ethical Hacker) methodology called Network Vulnerability Assessment Methodology were used to identify weak points in the nodes of the LAN infrastructure of the CSEDnet company in the Santo Domingo city. This methodology is within the CEH certification granted by the International Electronic Commerce Consultation Council (EC-Council). The Network Vulnerability Assessment is an examination of the possibilities of an attack on a network. The results indicate a great decrease in the captured packets (98.62%), after the implementation of the security policies proposed in this research